Assessment of the Difficulty Level of Science Questions Using the TIMSS Question Semantic Evaluation for Grade IV Elementary School Students - Romli, Muhammad; Arnyana, Ida Bagus Putu; Suastra, I Wayan (Jurnal Studi Guru dan Pembelajaran, 2025)
The main urgency of this study is to evaluate the semantic difficulty level of TIMSS questions for Grade IV students, considering the impact of semantic difficulty on students' understanding of concepts, which has not been extensively researched. The purpose of this study is to assess the semantic difficulty level of TIMSS questions among Grade IV students at SDN Parsanga II. This study uses a descriptive research method. The research population includes all Grade IV students at SDN Parsanga II, with a sample size of 30 students randomly selected from the population. The research instruments consist of TIMSS questions and a semantic assessment checklist regarding question difficulty levels. Data analysis is conducted quantitatively. The semantic difficulty level of TIMSS questions is determined based on the percentage of correct answers from students, and the question difficulty level is calculated using the percentage of correct answers from the entire student sample. The results of the study reveal that a high number of correct answers indicates a good understanding of the tested concepts, while a high number of incorrect answers suggests difficulties in understanding the concepts or errors in processing information. This analysis provides valuable insights into student performance and question difficulty levels. Based on this understanding, test results can be evaluated more comprehensively, thus improving the quality of learning. Educators can identify students' difficulties and needs in understanding the tested concepts and design appropriate interventions to enhance their understanding